RUSSIAN SOVIET FEDERATIVE SOCIALIST REPUBLIC’S POLICY TOWARD THE BUKHARA PEOPLE'S SOVIET REPUBLIC: STRATEGIC INTERESTS AND LEGAL FOUNDATIONS (1920–1924) - Sulton Jurayev (Bright Mind Publishing, 2025)
This article examines Soviet Russia’s policy toward the short-lived Bukhara People's Soviet Republic (1920–1924) through an analysis of historical developments, legal-constitutional frameworks, and Soviet geopolitical interests. In the wake of the Russian Revolution and Civil War, Bolshevik forces helped overthrow the Emirate of Bukhara and established a revolutionary regime that navigated a complex path between nominal independence and increasing Soviet control. Drawing on archival documents and scholarly sources, the study explores how Soviet Russia pursued strategic goals in Central Asia such as securing its southern frontier and spreading revolutionary influence while simultaneously crafting legal instruments (treaties, constitutions, and agreements) to legitimize its presence in Bukhara.
Keywords: Bukhara People’s Soviet Republic; Soviet Central Asia; Jadidism; National Delimitation; Geopolitics; Legal Status.